Coal Exploration-Fence Lake Project, Catron County, New Mexico - Marcie A. Greenberg; John C. Patton; R. Tim Thompson (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1985)
The Fence Lake Project is located in the Salt Lake coal field, an extension of the San Juan Basin. Geologic formations exposed in the Project area range in age from late Cretaceous to Quaternary. Coal is encountered in the Moreno Hill Formation (upper Cretaceous). Salt River Project (SRP) followed the basic textbook approach for the exploration, regional appraisal, detailed reconnaissance, detailed surface detailed and three dimensional sampling (physical exploration). SRP is exploring this property as a potential fuel source for the Coronado Generating Station. Therefore, for the physical exploration stage, the quality sampling program was designed from a utility company viewpoint to determine possible impacts to the Station. Exploration drilling was completed in spring, 1982; September, 1982, and summer, 1984. Engineering, environmental, and land acquisition studies - in the Summer, 1984 Program to more closely evaluate the potential Fence Lake Project coal supply option for the Coronado Generating Station. Studies, including drilling, are ongoing at this time.